The Students’ Vocabulary Understanding of British and American English - Hermini Parjas; Ardhy Supraba (Universitas Cokroaminoto Palopo, 2018)
This research aims to find out the students’ vocabulary understanding of American English and British English. The population of this research is the seventh semester students of Universitas Cokroaminoto Palopo which consists of three parallel classes. The total population is 120 students in academic year 2018/2019. Cluster random sampling technique is used to determine the sample. This research took one class as sample. The result of this research shows that the students’ vocabulary understanding of American and British English is fair. It can be seen by the result of mean score that is 52.67 which is classified into fair.